(untitled) (Eurasian Journal of Philology Science and Education, 2018)
This article is devoted to the linguopragmatic approach problem when translating the cultural-specific communication environment. The research is based on the material of modern Korean prose. The analysis of the main linguopragmatic components reflecting the interrelation of linguopragmatics and the theory of speech acts is carried out. The article also considers the relations between the explicit and implicit parts of the content of the speech product in Korean language. Statements in Korean were collected by the method of purposeful sampling from the works of modern Korean prose and served as the body material for the study. The methodological and theoretical basis of the study is the works of domestic and foreign scientists in the field of linguopragmatics, semantics, discourse theory, translation theory and practice. The hypothesis of this study is the assertion that the implicit part is an integral part of the overall meaning of the text, and it turns out to be pragmatically more significant. Research materials can be used to improve the methods of translation, as well as to develop lecture and practical courses on text linguistics, linguopragmatics, linguistic semantics and the practice of intercultural communication. The article was written within the framework of Korean Scholars Academy project (AKS-2017- INC-2230007) Korean literature (including the literature of the Koreans of Kazakhstan) and textbook specialist training